2005
DOI: 10.1073/pnas.0409549102
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of myasthenogenic T cell responses by a dual altered peptide ligand via CD4+CD25+-regulated events leading to apoptosis

Abstract: The myasthenogenic peptides p195–212 and p259–271 are sequences of the human acetylcholine receptor and were shown to induce myasthenia gravis-associated immune responses in mice. A dual altered peptide ligand (APL) composed of the two APLs of the myasthenogenic peptides inhibited, in vitro and in vivo , those responses. The aims of this study were to elucidate the events that follow the in vivo treatment with the dual APL and to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…IL-10 and IL-4 can actually reverse the T H 1 polarization of T cells, shifting from a IFN-g-producing (T H 1) to a IL-4-producing pattern, with evidence of clinical responses. 37 The up-regulation of TGF-b by altered peptide ligands 119R and 355L provided an additional hint about the functional activity of CD4 1 , CD25 1 regulatory T cells that are characterized by upregulated expression of cytotoxic T lymphocytee associated antigen, 4 intracellular and membrane TGF-b, and Foxp3-like other altered peptide ligands, 38 which needs further study. T-cell culture supernatants (1:100) from concentrations (10 and 100 g Á mL ÿ1 with 119R, 100 g Á mL ÿ1 with 355L) were more effective than ratios (1:10 and 1:1000) in inhibiting keratinocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 and IL-4 can actually reverse the T H 1 polarization of T cells, shifting from a IFN-g-producing (T H 1) to a IL-4-producing pattern, with evidence of clinical responses. 37 The up-regulation of TGF-b by altered peptide ligands 119R and 355L provided an additional hint about the functional activity of CD4 1 , CD25 1 regulatory T cells that are characterized by upregulated expression of cytotoxic T lymphocytee associated antigen, 4 intracellular and membrane TGF-b, and Foxp3-like other altered peptide ligands, 38 which needs further study. T-cell culture supernatants (1:100) from concentrations (10 and 100 g Á mL ÿ1 with 119R, 100 g Á mL ÿ1 with 355L) were more effective than ratios (1:10 and 1:1000) in inhibiting keratinocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same group of authors have shown that the dual APLs also induce CD4+CD25+ [56] as well as CD8+CD28- [57] T cells. The CD4+CD25+ T cells, which upregulate a 50-kDa ERK-like protein upon dual APL stimulation [58], seem to maximize their regulatory function by coexpressing CTLA-4 and - along with the secretion of TGF-β - induce apoptosis of effector T cells [59]. …”
Section: Influence Of Altered Peptide Ligands On T Cell Development Amentioning
confidence: 99%
“…As ERK signalling is usually linked to proliferation and differentiation, the upregulation of dpERK1,2 in T‐cells of immunized and dual APL‐treated mice, has not been expected based on the well‐documented inhibitory effects of the dual APL [5–7, 10]. Therefore, we attempted the identification of the population of T‐cells that might use dpERK1,2 in the inhibition of MG associated responses that are mediated by the dual APL.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, CD4 + CD25 + regulatory cells that are known to play a critical role in the maintenance of peripheral tolerance were found to be functionally involved in the suppressive action of the dual APL [8, 9]. Administration of the dual APL increased CD4 + CD25 + cells with regulatory characteristic markers [10, 11]. Depletion of CD4 + CD25 + cells diminished significantly the inhibitory effect observed after treatment with the dual APL [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation